PENGENDALIAN CACAT PRODUK DENGAN PENDEKATAN SIX SIGMA - Firman Ardiansyah Ekoanindiyo (Jurnal Ilmiah Dinamika Teknik, 2014)
The main factors that determine the performance of a company is the quality of goods and services in accordance with what is desired konsumenya. Therefore, organizations or companies need to know the consumer or subscriber and determine the needs and keinginannya.Metode Six Sigma is one method that is integral to quality improvement. This method proved to be effective to improve and enhance the quality of products and processes, and thus the number of defects detrimental to the company can be minimized and eventually expected profit of the company will increase as well. Six Sigma has steps, namely the application of DMAIC, which stands for Define - Measure - Analyze - Improve and Control. Methodology DMAIC improvement is a step that is very focused and continuous, wherein the step of the next steps are interrelated. Kata Kunci: Quality, Six Sigma Method, DMAIC